요양병원 요양보호사의 노인 구강건강관리 수행도 관련요인 - 최세은; Se-eun Choi; 한미아; Mi-ah Han; 박종; Jong Park; 류소연; So-yeon Ryu (Han'guk Ch'iwisaeng Hakhoe chi, 2017)
Objectives: Oral health management is important to improve the quality of life among the elderly. This study investigated the performance of elderly oral health management among some care workers in long-term-care hospitals. Methods: The study subjects were 174 care workers in 10 long-term-care hospitals. Data on general characteristics of care workers, attitude, recognition and knowledge of elderly health, performance of elderly oral health management were collected by a self-administered questionnaire. Data were analyzed through descriptive analysis, t-test, ANOVA, correlation and multiple regression analysis by using a SPSS version 23.0 statistical program. Results: The performance score of oral health management was 4.34±0.64 on the 5-point Likert scale. The subjects who exercised more than 2 times a month were significantly higher in their performance of elderly oral health management compared to subjects who did not exercise (β=0.232, p=0.035). And, the subjects who cared 10-19 persons were significantly higher in performance of elderly oral health management compared to subjects who cared more than 20 elderly (β=0.246, p=0.020). The oral health behavior of care worker (β=0.271, p<0.001) and the knowledge of oral health care (β=0.055, p=0.008) were positively related to the performance of elderly oral health management. Conclusions: The educational program designed to improve knowledge of care workers in accordance with the standard textbook for training care workers should be developed, and the long term education program should be reinforced to improve the performance for elderly oral health care. If care workers can care a proper number of old persons, they will give oral health care to them.